Desde la otra orilla: Alice Rühle-Gerstel y Otto Rühle. La experiencia del exilio político de izquierda en México 1935-1943 - Jacinto, Lizette (El Colegio de México, A.C., 2014)
This work seeks to critically analyze the intellectual conditions that the Rühle couple faced during their 1935-1943 political exile in Mexico, after fleeing German National Socialism. Both of them were renowned thinkers both in the academic and political fields, and both before and after World War I, specially during the so-called Weimar Republic. The paper highlights the personality of Alice Rühel-Gerstel, born in Prague to a Jewish family, for she would become a feminist and writer renowned in her time, but forgotten after Nazi censorship. This subject, as yet unpublished in Mexico, feeds on deep archive research carried out in Germany, the Netherlands, and Mexico.